PERAN DEMOGRAFI SEBAGAI VARIABEL MODERASI PADA PENGARUH LITERASI KEUANGAN DAN TEKNOLOGI INFORMASI TERHADAP PERILAKU KEUANGAN - Parulian Parulian; Nataliana Bebasari (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study seeks to examine the influence of financial literacy and information technology on the financial behavior of students with income demographics as moderators. The sample of this study was 95 respondents. Analyze the data using a structural equation model (PLS-SEM). The findings of the study prove that financial literacy and information technology have a significant positive impact on student financial behavior. In contrast, the demographics of the income have not been shown to have a significant impact on financial behavior. In addition, there is no significant evidence that income demographics are able to strengthen the influence of financial literacy on financial behavior and information technology on financial behavior. This means that students need to improve their financial knowledge and the benefits of using technology in order to have the ability to control and manage their finances more efficiently.